Estudio de prefactibilidad para la creación de una empresa de venta, instalación y capacitación en productos de automatización del hogar (domótica) en Lima Metropolitana - Huaman Talla, Jose Alonso (2022)
In the present investigation, different models and tools that were collected throughout the Industrial Engineering career were used, these allowed to have a scientific basis for the resolution of different unknowns that arose while the project, about the domotic service, was being developed. Among the main ones we have, in first place, the market study, where the target audience was determined and the behavior of different home automation products within the Peruvian market was analyzed to, later, project their sales in a 5-year panorama (9,190 packages by 2026). In second place, there is the study for the location of the company, where techniques such as confrontation tables and factor rankings were used to determine both the department and the district where the project will be established (Lince, Lima). Third, the study related to the company's facilities was carried out, in which, thanks to the Guerchet method and the "Manual para diseño de instalaciones manufactureras y de servicios", the tentative plan of the workplace was made (occupying a total area of 198 m2). Finally, economic-financial studies were carried out, which demonstrated the profitability of the home automation service, and it was also shown that it is more beneficial to externally finance 30% of the total investment (VAN: S /. 161,040.23 and TIR > COK).